Response of Soluble Transferrin Receptor and Iron-Related Parameters to Iron Supplementation in Elite, Iron-Depleted, Nonanemic Female Athletes - Pitsis, G. C.; Fallon, K. E.; Fallon, S. K.; Fazakerley, R. (Clinical Journal of Sport Medicine, 2004)
Objectives: To assess the effect of short-term iron supplementation on soluble transferrin receptor (sTfR) and the soluble transferrin receptor/log ferritin ratio in a group of elite, iron-depleted, nonanemic female athletes and to assess the relationship between soluble transferrin receptor and serum ferritin in a group of elite, iron-depleted female athletes. Design: A prospective, interventional study and an observation at 1 point in time. The primary inclusion criteria for each component of the study was serum ferritin less than 30 ng/mL and hemoglobin greater than 12 g/dL. The exclusion criteria were use of iron supplementation within 1 month of the initial assessment, acute or chronic infectious or inflammatory disease, hematological disorders, and recent musculoskeletal injury. Setting: The Department of Sports Medicine at the Australian Institute of Sport. Subjects: For the prospective study, 51, and for the observational study, 85 elite, iron-depleted (serum ferritin <30 ng/mL), nonanemic (hemoglobin <12 g/dL for the prospective study only) female athletes. Athletes were participants at the elite level in netball, basketball, gymnastics, rowing, volleyball, track and field, soccer, sailing, and cricket. Intervention: Ingestion of 1 iron tablet (325 mg dried ferrous sulfate, equivalent to 105 mg elemental iron) plus one 500-mg tablet of vitamin C each morning for 60 days. Results: Following supplementation, the following changes were statistically significant. Serum ferritin increased (19.7 to 37.4 ng/mL; P < 0.00005), serum transferrin decreased (3.34 to 3.16 g/L; P = 0.023), sTfR decreased (3.46 to 3.16 mg/L; P = 0.006), and sTfR/log ferritin index decreased (1.34 to 1.00; P < 0.00005). If it is assumed that iron stores are depleted when serum ferritin is less than 12 ng/mL and that sTfR could be expected to be elevated below that level of serum ferritin, the following figures can be calculated for the value of sTfR in relation to absent iron stores: sensitivity, 33%; specificity, 96%; positive predictive value, 50%; and negative predictive value, 92%. Conclusions: Short-term iron supplementation increases iron stores and leads to reductions in sTfR and the sTfR/log ferritin index in elite female athletes. sTfR is not an accurate predictor of serum ferritin less than 12 ng/mL in this group.